The Promotion of Single Sports Among Young People - Ochilov Gayrat Turdiyevich (Zien Journals, 2022)
This article contains the views of some experts on the study of individual wrestling and more effective management of the athlete's long-term training
Keywords: sports; human; athlete; wrestling